Induction of labour using foley catheter: traction versus no traction a randomized prospective study. - Nusee, Zalina; Ismail, Siti Mariam; Ab Rahman, Jamalludin; Ismail, Hamizah (2017)
Induction of labour is a common procedure in obstetrics, occuring in up to 30% of pregnancies. Both mechanical and pharmacological methods of induction of labour are available (Ryan& Mc Carthy, 2016) The ideal methods for cervical ripening are those that are safe to both fetus and mother, cost effective and do not require extensive monitoring. Catheter works by mechanically stretching the cervical canal causes release of prostaglandin which results in cervical changes (sciescione,2014). Studies showed transcervical catheter with traction (500gm & 1kg) increased the efficacy of induction.(Sciscione, 2014; Edwards, Szychowski et.al 2015; Henry et.al, 2013; Lin et al, 2007; Forgie et al , 2016).